Futures studies and the trends towards unity and diversity - Barbieri Masini, Eleonora (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 1997)
This article considers different approaches of Futures Studies to issues and favours the "vision" approach. It also looks at the role of Futures Studies in social sciences in general. It examines trends in the issue of unity and diversity, since the Second World War and some possible outcomes of such trends in the near future.